Analisis Tingkat Kesulitan Butir dan Kemampuan Matematika Siswa Berdasarkan Hasil Ujian Sekolah - Asmin Lukman; Hujairah Hi Muhammad (Peneliti.net, 2022)
This study aims to determine the level of difficulty of math items and the ability level of students based on the results of the School Examination. This research method uses a quantitative descriptive approach. The subjects in this study were 29 students of SMA IT Albina City of Ternate who took the school exams for the 2021/2022 academic year. There are 35 multiple choice items to be analyzed. The research instrument used student answer sheets. Data analysis used the Rasch model approach with the help of the Winstep program. The results showed that the acquisition of test reliability was 0.46 or included in the moderate category. The results of the analysis of the items using the winsteps program show that out of 35 items the difficulty index is between +2 and -2. There are no items that have an item difficulty index of more than +2 and less than -2. So it can be concluded that all items have a good category. The results of the analysis of students' mathematical abilities in answering questions with the Rasch model using the help of the Winstep program showed that out of 29 students, 21 students had moderate abilities and 8 students had low abilities.